Bilateral indirect carotid cavernous fistula post trivial injury- A case report - Mat Abu, Siti Hajar; Hashim, Hanizasurana; George, Tara Mary; Ngah, Norfariza; Hussein, Adil (Elsevier, 2013)
Fifty-seven years old Malay lady, post menopausal with co-morbid of diabetes mellitus and hypertension presented with three months history of bilateral painful red eyes associated with double vision. Examination revealed both eyes proptosis, corkscrew vessels with present of bruit, secondary narrow angle with raised intraocular pressure, 6th cranial nerve palsy, and bilateral venous stasis retinopathy. CT angiogram showed bilateral dilated superior ophthalmic veins with cerebral angiogram findings of bilateral indirect carotid cavernous fistula involving small meningeal vessels. Indirect or dural cavernous sinus Fistula can easily be missed or misdiagnosed. Trivial injury especially in the predisposing patient can initiate the occurrence.